Genetic contribution of breast cancer genes in women of black African origin - Ndiaye, Rokhaya; Diop, Jean Pascal Demba; Dem, Ahmadou; Dieye, Alioune (Frontiers in Genetics, 2023)
Breast cancer (BC) is an increasing public health issue worldwide. BC incidence and mortality rates are rising in transitioning countries in Africa, with the most rapid increase occurring in Sub-Saharan Africa (SSA). Female BC represents 25.8% of all cancer diagnosis in SSA. Early age at onset, high grade and triple negative tumors are hallmarks of BC in this region, associated with germline pathogenic variants in susceptibility genes. While several genes have been associated with genetic predisposition (BRCA1